Endothelin and sex hormones modulate the fibronectin synthesis by cultured human skin scleroderma fibroblasts. Issue 4 (24th October 2008) - Soldano, S; Montagna, P; Villaggio, B; Parodi, A; Gianotti, G; Sulli, A; Seriolo, B; Secchi, M E; Cutolo, M
Abstract : Objective: To evaluate the influence of endothelin-1 (ET-1) and sex hormones on cell proliferation and extracellular matrix (ECM) synthesis (ie, fibronectin, laminin) by cultured normal and scleroderma (SSc) human skin fibroblasts (FBs). Methods: Primary cultures of FBs were treated with ET-1 and sex hormones (17β-oestradiol or testosterone) for 24 h. Cell growth was analysed by methiltetrazolium salt test, ECM synthesis was evaluated by immunocytochemistry and western blot, both at 24 h. Results: In normal FBs, ET-1 and 17β-oestradiol, as well as their combination, increased cell growth (p<0.001, p<0.001, p<0.01 vs untreated cells (control), respectively) and fibronectin synthesis (p<0.05, p<0.05, p<0.01 vs control, respectively). By contrast, testosterone either alone or in combination with ET-1 did not influence cell proliferation, but decreased fibronectin synthesis (p<0.05, testosterone vs control). In SSc FBs, ET-1 and 17β-oestradiol alone or their combination induced an increased fibronectin synthesis (p<0.05, p<0.05, p<0.01 vs control, respectively). Unexpectedly, testosterone induced an increase of fibronectin synthesis (p<0.05 vs control). Conclusions: ET-1 and 17β-oestradiol seem to exert a profibrotic effect in normal and SSc culture FBs and might suggest their synergistic effect in the pathogenesis of the fibrotic process in SSc.